ANTIHYPERURESEMIA ACTIVITY OF ETHANOL EXTRACTS AND FRACTIONS OF NIPAH LEAF FRONDS (NYPA FRUTICANS. WURMB) - Raharjo, Danang; Dwi S, Anita; Aminnulloh, Muhammad (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
Hyperuresemia is a metabolite syndrome characterised by high levels of uric acid in the blood. Hyperuresmia in advanced stages can cause gout or pyrexia (a disease that affects the joints and causes joint damage), kidney stones, kidney damage, and hypertension. The nipah plant (Nypa fruticans. Wurmb) is traditionally used in the treatment of stomach pain, diabetes, fever, toothache, uric acid reduction and headache medicine. In general, the content of secondary metabolite compounds from nipah plants includes flavonoids, phenols, tannins, terpenois, steroids, alkaloids and saponins. The purpose of this study was to determine the xanthine oxidase inhibitory activity of ethanol extracts and fractions of nipah leaves (Nypa fruticans. Wurmb). Extraction process using maceration method with 96% ethanol solvent, fractionation using liquid-liquid partition method with separating funnel. . Testing the inhibition of xanthine oxidase enzyme activity in vitro using UV/VIS spectrophotometer. The results showed that ethanol extract, water fraction, ethyl acetate fraction and n-hexane fraction showed inhibitory activity of xanthine oxidase enzyme with IC50 values of 47.558 ± 2.862; 18.755 ± 3.821; 3.543 ± 1.440 and 110.213 ± 1.577 ppm, respectively. From the results of the study it can be concluded that ethanol extracts and fractions of nipah leaf fronds (Nypa fruticans.Wurmb) can inhibit the activity of xanthine oxidase enzyme with ethyl acetate fraction giving the highest inhibitory activity with IC50 value of 3,543±1,440 ppm.